Evaluación de medidas de gestión del tránsito a través de modelos de simulación vehicular: caso aplicado sobre el corredor urbano de la calle 72- Barranquilla (2019)
The population rate increases constantly and with it the demand in transport, the use of private vehicles has become the election par excellence due to the poor service provided by public transport, this is reflected in the vehicle capacity where the data show a composition in traffic of 75% for private vehicles, which represents the greatest volume, increasing the delay and travel times, congesting the road network. As an object of study, an emblematic urban corridor of the city was selected that presents these negative conditions, which is Calle 72, which, through microscopy simulation, will represent the real flow conditions through a software called Transmodeler to evaluate traffic management measures and so propose a solution and projecting it to 5, 10 and 20 years to see what levels of service the road offers over the course of time evaluating the effectiveness of the solution that in this case was to expand the urban corridor